PUSH AND PULL FACTORS FROM ASAHAN FISHERMAN DO MIGRATION IN KEPENGHULUAN PANIPAHAN LAUT PASIR LIMAU KAPAS SUBDISTRICT ROKAN HILIR REGENCY OF RIAU PROVINCE - Syafriyanto '; Ridar Hendri; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study conduted in november 2016 in Kepenghuluan Panipahan Laut Pasir Limau Kapas subdistrict Rokan Hilir Regency of Riau Province. This study aims to determinate, the factors are encouraging fishermen to migration in Kepenghuluan Panipahan Laut Pasir Limau Kapas subdistrict regency of Rokan Hilir, to determinate the factors are interesting fishermen to migration in Kepenghuluan Panipahan Laut Pasir Limau Kapas subdistrict regency of Rokan Hilir. The method used in this study is a survey method. The population in this study is all migrant fishermen who have lived in Kepenghuluan Panipahan Laut with the total population 15 respondents.Based on the results of the study that is the driving factor of fishermen to migrate due to reduced yield head seaward with an average 6,4 kg each day, the decrease of fisherman income in the area of origin with average fisherman income rp. 1.244.666/ month, the rights of fishermen are restricted so that the fishermen feel depressed and driven to get out of the area of origin, the establishment of communication between migrant fishermen with prospective migrant fishermen pushed out of the area of origin when hearing the potential news of the destination. Fishermen pull factors for migration in the region is many fishing catches with an average of 12.7 kg each day, high income in the destination area with an average rp. 3.534.000/month, freedom of fishermen in the destination area without any pressure, family factors that cause migrant fishermen are interested to move to an area of interest for their temporary shelter when migrant fishermen have not yet found employment.Keywords: Driving factors, towing, migration